The Factor of Women's Entrepreneurship in Competitiveness: Bibliometric Analysis - Setiani, Setiani; Sopiah, Sopiah (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2023)
This study aims to determine the factor of women entrepreneurship and analyze publication trends by knowing the number of articles, citations, most authors, and network clusters. This research is the first step to looking at existing research and finding research themes related to women's entrepreneurship. The method used is bibliometric analysis. Data was obtained through a database search, google scholar, by using the software Harzing's Publish or Perish. Initial results obtained as many as 509 articles were then extracted by only taking articles from reputable international publishers, so 72 articles were used. The study results show that the most frequently cited authors are Fauzi et al. (2020). Words often appear: women, entrepreneurship, women entrepreneur, women entrepreneurship, and studies. Bibliometric mapping supports the scientific explanation between probability theory and proof. Women's research Entrepreneurship can be developed more broadly on themes that appear few and have yet to be widely included in research in the last five years. Therefore, this research is expected to be a reference for further research on problems, training, challenges, cases, and rural women.